Rotator Cuff Tendon Healing Using Human Dermal Fibroblasts: Histological and Biomechanical Analyses in a Rabbit Model of Chronic Rotator Cuff Tears. Issue 13 (November 2021) - Lee, Ji-Hye; Kim, Yun Hee; Rhee, Sung-Min; Han, Jikhyon; Jeong, Hyeon Jang; Park, Joo Hyun; Oh, Joo Han; Jeon, Saewha
Background: Tenocytes derived from tendons have been reported to be effective in the treatment of rotator cuff tears through the expression of extracellular matrix proteins. Human dermal fibroblasts, known to express collagen types I and III as tenocytes do, may likely be substitutes for tenocytes to enhance healing rotator cuff tears. Purpose: To demonstrate the capability of human dermal fibroblasts to enhance healing of rotator cuff tears. Study Design: Controlled laboratory study. Methods: The cellular properties and expression profiles of growth factors were compared between human dermal fibroblasts and tenocytes. In both cell types, a series of extracellular matrix proteins were analyzed along with matrix metalloproteinases and tissue inhibitors of metalloproteinases involved in the collagenolytic system. A total of 35 rabbits were divided into 5 groups: normal (n = 2), saline control (n = 9), fibrin control (n = 9), low dose of human fibroblasts (HF-LD; n = 9), and high dose of human fibroblasts (HF-HD; n = 6). Cells were injected into the sutured lesions at 6 weeks after creation of bilateral rotator cuff tears, followed by histological and biomechanical analyses at 12 weeks. Results: Human dermal fibroblasts exhibited a protein expression pattern similar to that of tenocytes. More specifically, the expression levels of collagen types I and III were comparable between fibroblasts and tenocytes. The histological analysis of 30 surviving rabbits showed that collagen fibers were more continuous and better oriented with a more mature interface between the tendon and bone in the sutured lesions in the HF-LD and HF-HD groups. Most importantly, biomechanical strength, measured using the load to failure at the injection site, was 58.8 ± 8.9 N/kg in the HF-HD group, increasing by approximately 2-fold ( P = .0003) over the saline control group. Conclusion: Human dermal fibroblasts, showing cellular properties comparable with tenocytes, effectively enhanced healing of chronic rotator cuff tears in rabbits. Clinical Relevance: Human dermal fibroblasts can be used in place of tenocytes to enhance healing of rotator cuff tears.